### 21 Answers

Relevance

- 2 months ago
If a is -1/3, substitute "A" into "a3".

(-1/3)3

= -3/3

=-1

The value will be Negative 1

(Don't forget the minus sign)

- Login to reply the answers

- geezerLv 72 months ago
If a = -1/3 then a3 = -1

3 x 1/3 = 1 .. and then don't forget that it's 'minus'.

- Login to reply the answers

- 2 months ago
So basically you just have to multiply a by 3. So 3 × a and a is -1/3. And when you do that you will get -1.

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- Iggy RockoLv 72 months ago
Assuming you mean a^3,

(-1/3)^3 =

-1/3 * -1/3 * -1/3 =

-1/27

- Login to reply the answers

- 2 months ago
a = -1/3

a^3 = (-1/3)^3 (same as)

a^3 = (-1/3) x (-1/3) x (-1/3)

a^3 = (1/9) x (-1/3)

a^3 = -1/27

- Login to reply the answers

- TomVLv 72 months ago
Assuming "a3" is intended to be a³:

(-1/3)³ = (-1/3)(-1/3)(-1/3) = -1/27

- Login to reply the answers

- Jim MoorLv 72 months ago
I take that to be a³, your notation is throwing us off!

2) If a = -1/3 then a³ = ??

a^3 = a*a*a = (-1/3)*(-1/3)*(-1/3) = -1/27

- Login to reply the answers

Still have questions? Get your answers by asking now.